CSR as a Modern Marketing Communication Tool at the Threshold of the Third Millennium - Kristína Osúchová,; Jana Lešundáková,; Zdenka Kádeková,; Ingrida Košičiarová,; Adriana Mateášiková, (Communication Today, 2025)
The presented study focuses on the influence of marketing communication of CSR activities in the practice of food companies in Slovakia on the consumer behaviour of Generations X, Y, and Z. In the marketing activities of food companies, there is a noticeable shift towards considering social aspects, which increasingly influence consumer behaviour. This trend not only helps in solving many problems but also raises awareness of CSR activities. The theoretical and practical value of the article lies in the empirical confirmation of the reporting of CSR activities by food companies in the field of social marketing activities and their impact on consumer purchasing decisions, profit growth, brand awareness, and the building of corporate reputation through a questionnaire survey in which 946 respondents of Generation X, Y and Z took part. To evaluate the established hypotheses, statistical methods, and techniques such as Pearson’s Chi-square test of independence, the Kruskal-Wallis test and Chi-square test of independence, and One sample proportion Z test using Microsoft Excel and SPSS software were used.